Faktor Dan Dampak Perilaku Prokrastinasi Akademik Siswa Pada Mata Pelajaran PPKn Di SMP Negeri 7 Brebes - Meike Dwi Novita; Natal Kristiono (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Procrastination is the behavior of delaying academic assignments that are carried out intentionally by carrying out other activities that are not needed, so that work is hampered. The purpose of this study was to find out the general description, influencing factors and the impact resulting from students' academic procrastination behavior in Civics subjects at SMP Negeri 7 Brebes. This research method is descriptive qualitative. Data collection techniques using interviews, observation and documentation. Data validity techniques use source triangulation, techniques and extend observations, as well as data analysis techniques by collecting, presenting, reducing, and drawing conclusions of data. The results of the study showed that 1) The academic procrastination students of SMP Negeri 7 Brebes in PPKn subjects was high. Including the type of procrastination is Dysfunctional Procrastination, 2) Factors that affect academic procrastination, internal factors such as physical condition, psychology, time management, difficulty in concentrating and dislike of tasks. External factors such environmental, 3) Impacts arising from academic procrastination, internal effects such as feelings of guilt and regret for oneself. The external impact is that students do not complete assignments properly, learning outcomes are less than optimal and get a warning from the teacher.